A judicialização da política a partir do Supremo Tribunal Federal: sumula vinculante n° 13 e mandado de injunção - Lucas Zandona Guimaraes (2011)
This dissertation seeks to define the concept of judicialization of politics, judicial activism and politicization of the judiciary. From the jurisdiction of the Brazilian Supreme Court over the Constitutions of 1824, 1891, 1934, 1937, 1946, 1967, 1969 and 1988 proved to be the political character of the Court, without incurring any democratic deficit in its operation. It follows the Binding Decision No. 13 and Injunctive Writ as a manifestation of the judicialization of politics and judicial activism from the Supreme Court. The summary of that analysis was based on the Constitutional Emendation No. 45/2004, as well as its precedents of the Binding Decision No. 13 and the explicit principles of art. 37, caput, of the Constitution of 1988. The analysis of the Injunctive Writ was based on the assumption that the various interpretations of the Supreme Court gave to this constitutional remedy when judging the right to strike of civil servants from the Injunctive Writ No. 670, 708 and 712.